Cooperative Learning to Increase Students' English Self-Efficacy - Qomariah, Nurul; Wijaya, Annisa Larasati; Fashli, Mutiara Naura Raudhotul; Azkiya, Haifa Hilyatu; Dewi, Ratna Sari (Jurnal Basicedu, 2023)
The positive correlation between self-efficacy and students' achievement triggered researchers to find a learning model that could potentially improve students' English self-efficacy. Cooperative learning has the potential to do that, but there is limited substantiation suggesting that students' English self-efficacy can be positively affected by this learning model. Therefore, this study aimed to prove whether or not STAD cooperative learning contributes to enhancing students' English self-efficacy. This investigation used a quantitative methodology that implemented a one-group experimental study by utilizing pre- and post-treatment questionnaires. The sample consisted of 35 students enrolled in the eighth grade of a junior high school in Tangerang Selatan. The result of this study shows an insignificant difference between before and after treatment. This study also found a negligible effect size of cooperative learning on increasing students' English self-efficacy. Thus, this research gives new findings suggesting that STAD cooperative learning is not useful for increasing the students' English self-efficacy. As an implication, teachers can consider other learning models besides STAD cooperative learning in order to enhance students' English self-efficacy